Pengaruh Bimbingan Belajar Gratis Terhadap Motivasi Belajar Anak Di Desa Lopang Kecamatan Kembangbahu Kabupaten Lamongan - Kuswanto Kuswanto (JAMBIS : Jurnal Administrasi Bisnis, 2021)
Tutoring is the provision of assistance to children in solving learning problems that they do not understand. Free tutoring referred to in this study is the provision of assistance to school subjects that are not understood, approaches and services to children so that they recognize themselves and are able to make the right decisions in their learning activities. This research was conducted in Lopang village, Kembangbahu district, Lamongan district with 26 respondents. This study aims to analyze whether or not there is an effect of free tutoring on learning motivation, with the data collection methods used in this study were questionnaires, interviews and documentation. The approach used is quantitative with a simple linear regression model with SPSS. In SPSS the significance is written by default as 0.05. From the hypothesis test that has been carried out, it can be concluded that the free tutoring variable has a significant effect on children's learning motivation in Lopang village. This is shown in the Summary data where the R Square value or coefficient of determination (KD) is 0.090, which means that the independent variable or free tutoring affects the dependent variable as much as 9%, the remaining 91% is influenced by other factors. With a value (Sig.) of 0.138, which means a probability value greater than 5%, which is 0.05, it indicates that Free Tutoring has no effect on Learning Motivation.